2022
DOI: 10.3389/fcimb.2022.991400
|View full text |Cite
|
Sign up to set email alerts
|

Large gap between attitude and action in tuberculosis preventive treatment among tuberculosis-related healthcare workers in eastern China

Abstract: Healthcare workers (HCWs) are at a high risk for latent tuberculosis infection (LTBI) because of occupational exposure, and the attitudes and behaviors of frontline tuberculosis (TB)-related HCWs toward preventive treatment of LTBI in eastern China remain unknown. This study aimed to explore the attitudes and actual behaviors of TB-related HCWs toward TB preventive treatment (TPT) and to analyze the relevant factors influencing the attitudes of HCWs. A stratified random sample of 28 TB-designated hospitals was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The outcomes of this study disclosed that 53.5% of the HCWs serving in the selected teaching hospital had positive intention to receive LTBI treatment. The reported figure, however, was lower than that reported in 2017 for the Eastern China context displaying 62.3% willingness to receive LTBI treatment [ 46 ]. In India, 73.5% of non-HCWs with TB close contact disclosed positive intention to receive LTBI treatment [ 47 ].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The outcomes of this study disclosed that 53.5% of the HCWs serving in the selected teaching hospital had positive intention to receive LTBI treatment. The reported figure, however, was lower than that reported in 2017 for the Eastern China context displaying 62.3% willingness to receive LTBI treatment [ 46 ]. In India, 73.5% of non-HCWs with TB close contact disclosed positive intention to receive LTBI treatment [ 47 ].…”
Section: Discussionmentioning
confidence: 69%
“…Meanwhile, a higher percentage of Indians had stronger and more positive intent to receive LTBI treatment because of their close contact with TB patients in their households. Evidently, the two studies from India and Eastern China had samples that were in close contact with TB patients or worked around them [ 46 , 47 ]. Such a situation led the samples to have a high willingness to seek LTBI treatment stemming from high susceptibility to contracting TB [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals receiving TPT bear the risk of adverse effects such as severe or even fatal drug-induced hepatitis 28. Unfortunately, TPT coverage is low even in HCWs in China 29. In addition, potent new diagnostic tools, such as M. tuberculosis culturing and Xpert MTB/RIF tests, are limited to major hospitals 30.…”
Section: Discussionmentioning
confidence: 99%
“…28 Unfortunately, TPT coverage is low even in HCWs in China. 29 In addition, potent new diagnostic tools, such as M. tuberculosis culturing and Xpert MTB/RIF tests, are limited to major hospitals. 30 According to our study, vaccination with Vaccae is insufficient to control the disease to meet the WHO's goals.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of PrEP pills has been associated with liver and kidney problems, as well as decreased bone density. Additionally, a previous study conducted in eastern China found that healthcare workers chose side effects as the main reason for being unwilling to accept tuberculosis prevention treatment [ 68 ]. Furthermore, due to traditional cultural beliefs about medicine, it is widely acknowledged in China that all drugs have some toxicity and that individuals are unwilling to take medicine until they have symptoms, which also acts as a roadblock to PrEP uptake among MSM at high risk of HIV infection [ 69 ].…”
Section: Discussionmentioning
confidence: 99%